Pan-continental assessment of socioeconomic and environmental predictors of PFAS occurrence in European rivers from a harmonised monitoring study - Jun Li; Alistair B.A. Boxall; Caroline Swan; Selwyn Hoeks; Racliffe W.S. Lai; John L. Wilkinson; Recep C. Altinbag; Åsa Arrhenius; Roman Ashauer; Thomas Backhaus; Besnik Baraj; Vasiliki G. Beretsou; et al. (Water Research, 2026)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

The many ages of Triton: New crater counts on the Voyager high-resolution image sequence and implications for impactor provenance - William B. McKinnon; Kelsi N. Singer; Stuart J. Robbins; Michelle R. Kirchoff; Simon B. Porter; Paul M. Schenk; Ted Stryk; Jeffrey M. Moore (Icarus, 2024)

The contribution of nearshore oceanography to temporal variation in larval dispersal - Katrina A. Catalano; Elizabeth J. Drenkard; Enrique N. Curchitser; Allison G. Dedrick; Michelle R. Stuart; Humberto R. Montes; Malin L. Pinsky (Ecology, 2024)
Patterns of population connectivity shape ecological and evolutionary phenomena from population persistence to local adaptation and can inform conservation strategy. Connectivity patterns emerge from the interaction of individual behavior with a complex and heterogeneous environment. Despite ample observation that dispersal patterns vary through time, the extent to which variation in the physical environment can explain emergent connectivity variation is not clear. Empirical studies of its contribution promise to illuminate a potential source of variability that shapes the dynamics of natural populations. We leveraged simultaneous direct dispersal observations and oceanographic transport simulations of the clownfish Amphiprion clarkii in the Camotes Sea, Philippines, to assess the contribution of oceanographic variability to emergent variation in connectivity. We found that time‐varying oceanographic simulations on both annual and monsoonal timescales partly explained the observed dispersal patterns, suggesting that temporal variation in oceanographic transport shapes connectivity variation on these timescales. However, interannual variation in observed mean dispersal distance was nearly 10 times the expected variation from biophysical simulations, revealing that additional biotic and abiotic factors contribute to interannual connectivity variation. Simulated dispersal kernels also predicted a smaller scale of dispersal than the observations, supporting the hypothesis that undocumented abiotic factors and behaviors such as swimming and navigation enhance the probability of successful dispersal away from, as opposed to retention near, natal sites. Our findings highlight the potential for coincident observations and biophysical simulations to test dispersal hypotheses and the influence of temporal variability on metapopulation persistence, local adaptation, and other population processes.

How to prioritize species recovery after a megafire - Michelle Ward; Josie Carwardine; James E. M. Watson; Anna Pintor; Stephanie Stuart; Hugh P. Possingham; Jonathan R. Rhodes; Alexander R. Carey; Nancy Auerbach; April Reside; Chuan Ji Yong; Ayesha I. T. Tulloch (Conservation Biology, 2022)
Due to climate change, megafires are increasingly common and have sudden, extensive impacts on many species over vast areas, leaving decision makers uncertain about how best to prioritize recovery. We devised a decision‐support framework to prioritize conservation actions to improve species outcomes immediately after a megafire. Complementary locations are selected to extend recovery actions across all fire‐affected species’ habitats. We applied our method to areas burned in the 2019−2020 Australian megafires and assessed its conservation advantages by comparing our results with outcomes of a site‐richness approach (i.e., identifying areas that cost‐effectively recover the most species in any one location). We found that 290 threatened species were likely severely affected and will require immediate conservation action to prevent population declines and possible extirpation. We identified 179 subregions, mostly in southeastern Australia, that are key locations to extend actions that benefit multiple species. Cost savings were over AU$300 million to reduce 95% of threats across all species. Our complementarity‐based prioritization also spread postfire management actions across a wider proportion of the study area compared with the site‐richness method (43% vs. 37% of the landscape managed, respectively) and put more of each species’ range under management (average 90% vs. 79% of every species’ habitat managed). In addition to wildfire response, our framework can be used to prioritize conservation actions that will best mitigate threats affecting species following other extreme environmental events (e.g., floods and drought).

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Persistence of a reef fish metapopulation via network connectivity: theory and data - Allison G. Dedrick; Katrina A. Catalano; Michelle R. Stuart; J. Wilson White; Humberto R. Montes; Malin L. Pinsky (Ecology Letters, 2021)
Determining metapopulation persistence requires understanding both demographic rates and patch connectivity. Persistence is well understood in theory but has proved challenging to test empirically for marine and other species with high connectivity that precludes classic colonisation–extinction dynamics. Here, we assessed persistence for a yellowtail anemonefish ( Amphiprion clarkii ) metapopulation using 7 years of annual sampling data along 30 km of coastline. We carefully accounted for uncertainty in demographic rates. Despite stable population abundances through time and sufficient production of surviving offspring for replacement, the pattern of connectivity made the metapopulation unlikely to persist in isolation and reliant on immigrants from outside habitat. To persist in isolation, the metapopulation would need higher fecundity or to retain essentially all recruits produced. This assessment of persistence in a marine metapopulation shows that stable abundance alone does not indicate persistence, emphasising the necessity of assessing both demographic and connectivity processes to understand metapopulation dynamics.

Quantifying dispersal variability among nearshore marine populations - Katrina A. Catalano; Allison G. Dedrick; Michelle R. Stuart; Jonathan B. Puritz; Humberto R. Montes; Malin L. Pinsky (Molecular Ecology, 2021)
Dispersal drives diverse processes from population persistence to community dynamics. However, the amount of temporal variation in dispersal and its consequences for metapopulation dynamics is largely unknown for organisms with environmentally driven dispersal (e.g., many marine larvae, arthropods and plant seeds). Here, we used genetic parentage analysis to detect larval dispersal events in a common coral reef fish, Amphiprion clarkii , along 30 km of coastline consisting of 19 reef patches in Ormoc Bay, Leyte, Philippines. We quantified variation in the dispersal kernel across seven years (2012–2018) and monsoon seasons with 71 parentage assignments from 791 recruits and 1,729 adults. Connectivity patterns differed significantly among years and seasons in the scale and shape but not in the direction of dispersal. This interannual variation in dispersal kernels introduced positive temporal covariance among dispersal routes that theory predicts is likely to reduce stochastic metapopulation growth rates below the growth rates expected from only a single or a time‐averaged connectivity estimate. The extent of variation in mean dispersal distance observed here among years is comparable in magnitude to the differences across reef fish species. Considering dispersal variation will be an important avenue for further metapopulation and metacommunity research across diverse taxa.

Host Identity as a Driver of Moss-Associated N2 Fixation Rates in Alaska - Julia E. M. Stuart; Hannah Holland-Moritz; Lily R. Lewis; Mélanie Jean; Samantha N. Miller; Stuart F. McDaniel; Noah Fierer; José Miguel Ponciano; Michelle C. Mack (Ecosystems, 2021)

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Novel bacterial lineages associated with boreal moss species - Hannah Holland‐Moritz; Julia Stuart; Lily R. Lewis; Samantha Miller; Michelle C. Mack; Stuart F. McDaniel; Noah Fierer (Environmental Microbiology, 2018)
Summary Mosses are critical components of boreal ecosystems where they typically account for a large proportion of net primary productivity and harbour diverse bacterial communities that can be the major source of biologically‐fixed nitrogen in these ecosystems. Despite their ecological importance, we have limited understanding of how microbial communities vary across boreal moss species and the extent to which local site conditions may influence the composition of these bacterial communities. We used marker gene sequencing to analyze bacterial communities associated with seven boreal moss species collected near Fairbanks, AK, USA. We found that host identity was more important than site in determining bacterial community composition and that mosses harbour diverse lineages of potential N 2 ‐fixers as well as an abundance of novel taxa assigned to understudied bacterial phyla (including candidate phylum WPS‐2). We performed shotgun metagenomic sequencing to assemble genomes from the WPS‐2 candidate phylum and found that these moss‐associated bacteria are likely anoxygenic phototrophs capable of carbon fixation via RuBisCo with an ability to utilize byproducts of photorespiration from hosts via a glyoxylate shunt. These results give new insights into the metabolic capabilities of understudied bacterial lineages that associate with mosses and the importance of plant hosts in shaping their microbiomes.

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Biomarkers of Fruit and Vegetable Intake in Human Intervention Studies: A Systematic Review - Francina R. Baldrick; Jayne V. Woodside; J. Stuart Elborn; Ian S. Young; Michelle C. McKinley (Critical Reviews in Food Science and Nutrition, 2011)